Cloning, Expression, Characterization, and Antioxidant Protection of Glutaredoxin3 From Psychrophilic Bacterium Psychrobacter sp. ANT206 - Wang, Yatong; Hou, Yanhua; Wang, Quanfu (Frontiers in Microbiology, 2021)
Glutaredoxins (Grxs) are proteins that catalyze the glutathione (GSH)-dependent reduction of protein disulfides. In this study, a Grx-related gene (264 bp), encoding a Ps-Grx3, was cloned from Psychrobacter sp. ANT206. Sequence analysis indicated the presence of the active site motif CPYC in this protein. Homology modeling showed that Ps-Grx3 had fewer hydrogen bonds and salt bridges, as well as a lower Arg/(Arg + Lys) ratio than its mesophilic homologs, indicative of an improved catalytic ability at low temperatures. Site-directed mutagenesis demonstrated that Cys13, Pro14, and Cys16 sites were essential for the catalytic activity of Ps-Grx3, while circular dichroism (CD) spectroscopy confirmed that point mutations in these amino acid residues led to the loss or reduction of enzyme activity. Furthermore, analysis of the biochemical properties of Ps-Grx3 showed that the optimum temperature of this enzyme was 25 °C. Importantly, Ps-Grx3 was more sensitive to tBHP and CHP than to H2O2, and retained approximately 40% activity even when the H2O2 concentration was increased to 1 mM. Regarding substrate specificity, Ps-Grx3 had a higher affinity for HED, L-cystine, and DHA than for S-sulfocysteine and BSA. We also investigated the DNA-protective ability of Ps-Grx3 using the pUC19 plasmid, and found that Ps-Grx3 could protect supercoiled DNA from oxidation-induced damage at 15 ℃ for 1.5 h. This study provides new insights into the structure and catalytic activity of a cold-adapted Grx3.